COMMUNITY SATISFACTION LEVEL IN RECEIVING RECOMMENDATION SERVICES JKMM (HEALTH INSURANCE FOR THE POOR) AT THE SOCIAL SERVICE SIDOARJO REGENCY - Dwiky Darma Pramudya (MAP Observer: Jurnal Penelitian Administrasi Publik, 2023)
Service satisfaction is the result of public opinion and evaluation of the performance of services provided by public service providers. Community Satisfaction Index (IKM) is data and information about the level of community satisfaction obtained from quantitative and qualitative measurement results of public opinion in obtaining services from public service providers and comparing their expectations and needs. This study analyzes the influence of service as a factor that influences people's satisfaction. According to Kepmen PAN No. 25 of 2004 concerning the Community Satisfaction Index (IKM), there are 14 matters related to the performance and services performed by service officers, including service procedures, suitability of requirements, employee clarity, employee discipline, employee responsibility, employee capabilities, service speed, service fairness, employee courtesy, cost fairness, cost certainty, schedule certainty, environmental comfort, and service security. This research was conducted to analyze the value of these variables, as well as their influence on community satisfaction. Community satisfaction is very influential in the field of services at the Sidoarjo Regency Social Service in managing the JKMM (Health Insurance for the Poor) recommendation letter. The quality of service at the Sidoarjo Regency Social Service is one of the important factors in utilizing the JKMM recommendation letter service at the Sidoarjo Regency Social Service.